2019
DOI: 10.1080/19336950.2019.1615824
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid interactions with ion channels and receptors

Abstract: Cannabidiol (CBD), the non-psychoactive component of Cannabis sativa , acts on a diverse selection of membrane proteins with promising therapeutic potential in epilepsy and chronic pain. One such protein is the voltage-gated sodium channel (Na v ). CBD shows a lack of specificity for sodium channels; however, the method of interaction is still unknown. In this review, we will outline the studies that report reproducible results of CBD and other cannabinoids changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 36 publications
0
64
0
Order By: Relevance
“…Specifically, this antagonism on CB2 receptors inhibits immune cell migration and might explain the anti-inflammatory effects of CBD, as well as the attenuation of THC psychoactive side-effects [13]. Recent studies have also shown that CBD can interact with a wide range of other targets, such as sodium, potassium, and calcium channels, and serotonin and glycine receptors, independently from the CB1 and CB2 receptors [14].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, this antagonism on CB2 receptors inhibits immune cell migration and might explain the anti-inflammatory effects of CBD, as well as the attenuation of THC psychoactive side-effects [13]. Recent studies have also shown that CBD can interact with a wide range of other targets, such as sodium, potassium, and calcium channels, and serotonin and glycine receptors, independently from the CB1 and CB2 receptors [14].…”
Section: Discussionmentioning
confidence: 99%
“…Both of these diseases are rare early-onset epilepsies associated with Navs, with Dravet patients often having mutations in the hNav1.1 gene SCN1A ( Marini et al, 2011 ). Despite a significant amount of evidence reporting on the effectiveness of CBD for treating epileptic conditions ( Cross et al, 2017 ; Devinsky et al, 2018 ), the molecular basis of its target interactions with ion channels and receptors still remains unclear ( Watkins, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CBD has been shown to attenuate seizures and social deficits in a mouse model of Dravet syndrome (Kaplan et al, 2017). Despite a significant amount of evidence reporting on the effectiveness of CBD for treating epileptic conditions (Cross et al, 2017;Devinsky et al, 2018), the molecular basis of its target interactions remain unclear (Watkins, 2019).…”
Section: Introductionmentioning
confidence: 99%